2007
DOI: 10.20452/pamw.67
|View full text |Cite
|
Sign up to set email alerts
|

Tryptase- and chymase-positive mast cells as possible prognostic factor in patients with Hodgkin’s lymphoma

Abstract: Objectives. The aim of the study was to identify potential prognostic factors in Hodgkin's lymphoma-HL patients by means of assessment of the influence of mast cells on clinical characteristics of the disease. Patients adn methods. Tryptase-and chymase-positive mast cell density was assessed in order to correlate it with histological type, staging, sex and age of patients. Tissue specimens were taken from a group of 72 patients treated for Hodgkin's lymphoma in the Department of Internal Medicine and Oncologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…And human tumors in which MCD is supposed to correlate with a poor prognosis include HL, diffuse large B-cell lymphoma, follicular and angioimmunoblastic T-cell lymphoma (Molin, 2002;Gratzinger, 2007;Ribatti, 2009;Taskinen, 2010;). Amazingly, in some studies, human tumors in which MCD is supposed to correlate with a good prognosis include HL, diffuse large B-cell lymphoma, and follicular lymphoma (Koster, 2005;Hedström, 2007;Rygoł, 2007;Ribatti, 2009;). Although it is hard to explain these conflicting results above and in the literature, they may be associated with different methodologies used in studies such as timing of biopsy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…And human tumors in which MCD is supposed to correlate with a poor prognosis include HL, diffuse large B-cell lymphoma, follicular and angioimmunoblastic T-cell lymphoma (Molin, 2002;Gratzinger, 2007;Ribatti, 2009;Taskinen, 2010;). Amazingly, in some studies, human tumors in which MCD is supposed to correlate with a good prognosis include HL, diffuse large B-cell lymphoma, and follicular lymphoma (Koster, 2005;Hedström, 2007;Rygoł, 2007;Ribatti, 2009;). Although it is hard to explain these conflicting results above and in the literature, they may be associated with different methodologies used in studies such as timing of biopsy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Yano et al (1999) reported that mast cell infiltration around gastric cancer cells correlates with tumor angiogenesis and metastasis. Normal mast cells have also been found to exist during the development of other soft tissue tumors such as malignant lymphoma and Hodgkin's lymphoma (Fukushima et al 2006;Hedstrom et al 2007;Rygol et al 2007). Chemical mediators released from mast cells were thought to be responsible for the enhanced proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%